Click Synthesis, Anticancer Activity and Molecular Docking Studies on Pyridazinone Scaffolds - El Malah, Tamer; Nour, Hany F.; Dehbi, Oussama; Abdel-Megeid, Farouk M.E.; Mahmoud, Abeer Essam El-Din; Ali, Mamdouh M.; Soliman, Salwa M. (Current Organic Chemistry, 2018)
A series of triazolo-pyridazinone derivatives were prepared through the standard click reactions of 4,6-diphenyl-2-(prop-2-yn-1-yl)pyridazin-3(2H)-one 1, possessing a free terminal alkyne group with a selection of substituted aryl azides 2-9. The cytotoxicity and in vitro anticancer investigation of the new compounds were conducted against four different human tumor cell lines, including breast adenocarcinoma MCF-7, hepatocellular carcinoma HepG2, lung cancer A549 and colon cancer HCT116 cell lines. The results showed that the compounds exerted their actions in MCF-7 and A549 via inhibition of the urokinase activity. The compound 17 showed potent anticancer activity compared with the activity of the standard anticancer drug, doxorubicin. Molecular docking studies were performed to support the activity data and predict the plausible mechanisms of the ligand-protein interactions.
Keywords: Trizolo-pyridazinone